2017
DOI: 10.1002/slct.201601110
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Fluorescent Biosensor for Creatinine Determination in Human Biofluids Based on Water Soluble Rhodamine B Dye‐Au3+ ions Conjugate

Abstract: Simple, ultrasensitive and selective diagnostic tool is required for the quantification of creatinine in human biofluids. To the best of our knowledge, we are reporting the second fluorescent as well as colorimetric biosensor for creatinine with a very good linear range. We have utilized a simple water soluble Rhodamine B dye as a probe because of its excellent emitting properties and quantum yield. As a colorimetric biosensor, the dye has selectively detected the Au3+ ions in a ratiometric aspect through ICT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…The level of creatinine ( Cr , see Figure ) in human bodily fluids is a widely applied clinical indicator for monitoring kidney and renal functions. , Creatinine is a metabolic waste product, being related to muscle activity, and any anomalous secretion due to organ malfunction leads inevitably to higher concentrations of Cr in blood serum and/or urine. Methods for molecular biosensing of creatinine using simple fluorescent probes or in combination with bioconjugates have been reported. While these latter approaches rely on unspecific interactions between creatinine and the probe molecule, supramolecular sensing offers distinct benefits for the design of selective and specific sensors by building on size, shape, and function complementarity between the receptor and analyte. Unfortunately, most synthetic receptors designed for creatinine binding are flat and edge-functionalized with divergent hydrogen bonding motifs. These characteristics make them a nonideal choice for supramolecular sensing design.…”
Section: Introductionmentioning
confidence: 99%
“…The level of creatinine ( Cr , see Figure ) in human bodily fluids is a widely applied clinical indicator for monitoring kidney and renal functions. , Creatinine is a metabolic waste product, being related to muscle activity, and any anomalous secretion due to organ malfunction leads inevitably to higher concentrations of Cr in blood serum and/or urine. Methods for molecular biosensing of creatinine using simple fluorescent probes or in combination with bioconjugates have been reported. While these latter approaches rely on unspecific interactions between creatinine and the probe molecule, supramolecular sensing offers distinct benefits for the design of selective and specific sensors by building on size, shape, and function complementarity between the receptor and analyte. Unfortunately, most synthetic receptors designed for creatinine binding are flat and edge-functionalized with divergent hydrogen bonding motifs. These characteristics make them a nonideal choice for supramolecular sensing design.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, in the computational work reported by Francois et al ., [28] a strong NH−S bond was observed. It is also reported that the strengths of NH−S and NH−O are dependent on the angle of the hydrogen bond [28] …”
Section: Resultsmentioning
confidence: 88%
“…The interaction between NH−S is considered weak compared to NH−O, because of the low electronegativity value of S (2.58) in comparison to O (3.40). Nonetheless, in the computational work reported by Francois et al ., [28] a strong NH−S bond was observed. It is also reported that the strengths of NH−S and NH−O are dependent on the angle of the hydrogen bond [28] …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…1 c—II. This is due to the gradual relaxation between BOBzBT 2 and the creatinine molecule 25 . Despite that, two BOBzBT 2 characteristic peaks as obtained previously, were preserved.…”
Section: Resultsmentioning
confidence: 99%